MATHEMATICAL MODELING OF EPILEPTOGENESIS PROCESS IN DIFFERENT AGE GROUPS Kalinin V. A. - V. A. Kalinin; I. A. Poverennova; E. M. Beketova; M. A. Gromakovskaya (Эпилепсия и пароксизмальные состояния)
Goal. To assess the state of epileptic system using mathematical modeling to monitor the effectiveness of the therapy of epilepsy  in  various  age  group.  Materialy and  methods.  It  conducts   research  on  visual  evoked  potentials  facing checkerboard  pattern in patients  with various forms  of epilepsy  in the young  and the elderly. We used  the original method  of  mathematical  analysis  of  the  results.  Results.  A study  of  evoked  potentials  to  evaluate the  stability of neurodynamic  system in terms  of the risk of an epileptic seizure.  Obtained significant differences  in the calculated indicators of a group of young patients with cerebral morphofunctional immaturity and a group of elderly patients with involutional changes. Normal values should be regarded as the ratio of positive and negative component (Sp / Sn) from 0.5 to 3.0. More than 3.0 determined  a high risk of seizures  in patients with brain immaturity, below 0.5 – the risk of seizures  in patients  with severe  cerebral involutional changes.  Conclusion.Using the algorithm described  in clinical practice as a supplementary  budget method with the routine EEG and video-EEG monitoring for epilepsy will predict an individual patient and change pharmacotherapy due time for the rapid achievement  of remission  counter. The process of generating an epileptic fit in each age group can be described with the use of the theory of unstable systems.